2011
DOI: 10.1111/j.1442-2042.2010.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of transurethral surgery for benign prostatic hyperplasia: A nationwide survey in Japan

Abstract: Objectives: Various types of minimally invasive surgical treatments, including transurethral resection of prostate (TURP), are being carried out in Japan for patients with benign prostatic hyperplasia (BPH). The aim of the present study was to elucidate the current status of perioperative care for these treatments by carrying out a nationwide survey. Methods: Assisted by the Japanese Endourology and ESWL Association, perioperative data from 157 institutions participating in this survey were collected and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
2
17
1
3
Order By: Relevance
“…TUEB was developed to maintain the equivalent effi cacy of adenoma enucleation, such as open prostatectomy or HoLEP, with excellent haemostasis. According to a nationwide survey in Japan, which investigated the trend in surgical procedures for BPH in 2009 including 20 413 operations, endosurgical enucleation, such as HoLEP and TUEB, has dramatically increased, becoming the second most common treatment ( n = 3416; 16.7%) after standard TURP and TURis ( n = 14 799; 72.5%) [ 20 ] .…”
Section: T U E B a N D T R A N S U R E T H R A L R E S E C T I O N I mentioning
confidence: 99%
“…TUEB was developed to maintain the equivalent effi cacy of adenoma enucleation, such as open prostatectomy or HoLEP, with excellent haemostasis. According to a nationwide survey in Japan, which investigated the trend in surgical procedures for BPH in 2009 including 20 413 operations, endosurgical enucleation, such as HoLEP and TUEB, has dramatically increased, becoming the second most common treatment ( n = 3416; 16.7%) after standard TURP and TURis ( n = 14 799; 72.5%) [ 20 ] .…”
Section: T U E B a N D T R A N S U R E T H R A L R E S E C T I O N I mentioning
confidence: 99%
“…For example, Japan is characterized by a longer length of stay for acute care patients compared with Western countries. 27,28 A survey on perioperative management of TURP around 2007 in Japan 29 reported that the postoperative length of stay for M-TURP and TURis was 8.3 -7.8 and 7.1 -3.6 days, respectively, and documented that most Japanese patients want to stay hospitalized until their urinary catheter is removed, because the national health insurance system covers these long postoperative stays.…”
mentioning
confidence: 99%
“…Reports on the incidence of recatheterization after surgery for treatment of BPH have varied. Failure to void after TURP is reported to occur in 0.5% to 21% of patients [6-12]. Failure to void after HoLEP is reported to occur in 1.4% to 12.1% of patients [12-17].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of recatheterization after TURP has been reported as 0.5% to 21% of patients [6-12], and that after HoLEP has been reported as 5% to 9% [12-17]. Because of increased patient discomfort, increased duration of hospitalization, and risk of secondary urinary tract infection [18] caused by the catheter, recatheterization is a complication that surgeons want to avoid.…”
Section: Introductionmentioning
confidence: 99%